2015
DOI: 10.1007/s10554-015-0714-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of quantitative bright spots analysis in patients with acute coronary syndrome: an optical coherence tomography study

Abstract: To investigate the clinical significance of bright spots in coronary plaque detected by optical coherence tomography (OCT) in patients with coronary artery disease. We identified 112 patients [acute coronary syndromes (ACS): n = 50, stable angina pectoris (SAP): n = 62] who underwent OCT imaging of the culprit lesion. A novel OCT algorithm was applied to detect bright spots representing the juxtaposition of a variety of plaque components including macrophages. The density of bright spots within the most superf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
1
4
0
1
Order By: Relevance
“…Therefore, at present, we cannot conclude on the relationship between CUC and fibrous cap thickness without additional longitudinal observations. Previous studies have reported the utility of OCT to detect macrophages the in coronary plaque and quantitatively evaluate the extent of macrophage accumulation [29,31]. In this study, we revealed there was an inverse relationship between CUC and the macrophage score assessed according to previously described methods [27].…”
Section: Discussionsupporting
confidence: 53%
“…Therefore, at present, we cannot conclude on the relationship between CUC and fibrous cap thickness without additional longitudinal observations. Previous studies have reported the utility of OCT to detect macrophages the in coronary plaque and quantitatively evaluate the extent of macrophage accumulation [29,31]. In this study, we revealed there was an inverse relationship between CUC and the macrophage score assessed according to previously described methods [27].…”
Section: Discussionsupporting
confidence: 53%
“…(Figure 5A) While OCT has not been proven to distinguish between active and inactive macrophages (94), bright spots do have a strong correlation with inflammation measured by hsCRP (95). Bright spot density is significantly higher in lipid plaques compared to fibrous plaques and plaques with TCFA show a trend toward higher bright spot density (95). Moreover, bright spot density is also significantly higher in plaques with rupture than those without (95).…”
Section: Optical Coherence Tomography (Oct)mentioning
confidence: 96%
“…Macrophages scatter light efficiently, which creates signal-rich regions called bright spots with a cast shadow behind (93). (Figure 5A) While OCT has not been proven to distinguish between active and inactive macrophages (94), bright spots do have a strong correlation with inflammation measured by hsCRP (95). Bright spot density is significantly higher in lipid plaques compared to fibrous plaques and plaques with TCFA show a trend toward higher bright spot density (95).…”
Section: Optical Coherence Tomography (Oct)mentioning
confidence: 96%
“…Активированные макрофаги вырабатывают повышенное количество матричных металлопротеиназ и катепсинов, которые умень-шают выработку коллагена и индуцируют апоптоз гладкомышечных клеток, что может провоциро-вать разрыв бляшки [14]. Плотность инфильтрации макрофагов в фиброатероме с тонкой покрыш-кой была выше, чем в бляшках без фиброатеромы (0,57±0,50% против 0,41±0,31%, p=0,08), и выше у пациентов с ОКС, чем со стабильной стенокарди-ей (0,51±0,43% против 0,37±0,26%, p=0,04) [15]. Более поверхностное расположение макрофагов (<50 мкм от поверхности сосуда) в сравнении с от-носительно глубоким расположением (>50 мкм от поверхности сосуда) в ОКС-зависимых артериях было предиктором их повреждения (p=0,035) [16].…”
Section: окт в диагностике нестабильной бляшкиunclassified